Pengaruh Core Stability Exersice Terhadap Penurunan Risiko Jatuh Lansia - Wijaya, Amwa Wigati; , Dwi Rosella KS, M.Fis (2016)
Background: 30-50% of the elderly have experienced falls and 40% experienced recurrent falls incident ( WHO ) . The incidence of falls in the elderly can be affected by two things: the faktors intrinsic and extrinsic faktors . One faktor is melemhnya extrinsic muscles of the body (core ) which is one of the faktors that are important in postural set . By exercising the muscles of the body (core ) through core stability exercise , can improve muscle weakness in muscles of the body that increases the stability in processing pergerkan thus achieved an increase in the balance of den decrease the risk of falls. Objective: Knowing effect of core stability exercises to decrease the risk of falls in the elderly in posyandu Nilasari , Kartasura. Methods: This research is a quasi experiment with pre test and post test two group design , the sample group I given core stability exercise and group II were not given core stability exercise for 4 weeks with a frequency 2x a week. Measurement of the value of the risk of falls in the elderly do with time up and go test ( TUG ) . Data analysis using Wilcoxon test. Results: There is a core stability exercise influence on the value of the risk of falls in the elderly after the performed statistical tests obtained using Wilcoxon test p-value of 0.004 with a success rate of 0.2%. Conclusion: There is a decrease in the level of risk of falls in the elderly in posyandu Nilasari , kartusura.